One-pot thermal evaporation synthesis of CdS-RGO hetrostructure and its field emission study - Bansode, Sanjeewani R.; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J. (2015 28TH International Vacuum Nanoelectronics Conference (IVNC), 2015)
CdS-RGO heterostructure was synthesized by thermal evaporation method. The as-synthesized CdS-RGO heterostructure was characterized using X-ray Diffraction, SEM, and EADX, before field emission (FE) studies. The FE characteristics of a planar emitter made up of as-synthesized CdS-RGO heterostructures were measured at the base pressure 1x10(-8) mbar. The synthesized CdS-RGO heterostructure emitter is found to deliver a current density similar to 70 mu A/cm(2) at an applied electric field of similar to 4.7 V/mu m. Moreover, the nanocomposite shows excellent emission stability without significant current degradation making CdS-RGO heterostructure as a promising electron source for practical applications in various vacuum nano-microelectronic devices.

Oxidative and membrane stress-mediated antibacterial activity of WS2 and rGO-WS2 nanosheets - Navale, Govinda R.; Rout, Chandra Sekhar; Gohil, Kushal N.; Dharne, Mahesh S.; Late, Dattatray J.; Shinde, Sandip S. (RSC Advances, 2015)
Graphene-based materials have strong cytotoxic attributes against bacteria due to their unique physicochemical properties. We examined the antibacterial activities of nanosheets of the graphene analogue tungsten disulphide (WS2) and a composite of reduced graphene oxide-tungsten disulphide (rGO-WS2), comparing them with reduced graphene oxide (rGO) by a time and concentration dependent viability assay and growth curve studies against four bacterial strains: Gram negative Escherichia coli (E. coli) and Salmonella typhimurium (S. typhimurium), and Gram positive Bacillus subtilis (B. subtilis) and Staphylococcus epidermidis (S. epidermidis). The nanosheets of the rGO-WS2 composite caused a more significant retardation in bacterial growth and inhibitory effect on the tested bacterial strains than WS2, followed by rGO. The tested E. coli and B. subtilis strains were more susceptible than the other strains. A mechanistic study revealed that rGO and WS2 did not produce the superoxide anion (O-2(-)) or reactive oxygen species (ROS), but the nanocomposite of rGO-WS2 did produce both. However, all these materials did oxidize glutathione, which serves as a redox state mediator in bacteria. We conclude that the antimicrobial mechanism is due to the combined effect of initial cell deposition on the rGO-WS2 materials, the membrane stress due to direct contact with the nanosheets, and the produced superoxide anion-independent oxidation mechanisms. The beneficial aspects of the physicochemical properties of rGO-WS2, such as its size and conductivity, can be precisely customized to reduce its health and environmental risk factors.

Observation of enhanced field emission properties of Au/TiO2 nanocomposite - Patil, Girish P.; Bagal, Vivekanand S.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Applied Physics A-Materials Science & Processing, 2016)
Simple and low-cost method of thermal annealing was used to decorate Gold (Au) nanoparticles on aligned TiO2 nanotubes. The aligned TiO2 nanotubes were decorated by Au nanoparticles with an average diameter of 9, 18 and 28 nm (aligned TiO2 nanotubes referred as specimen A and TiO2 nanotubes decorated by Au nanoparticles with average diameter of 9, 18 and 28 nm are referred as specimen B, C and D, respectively). The detailed characterization such as structural, morphological and elemental analysis of TiO2 and Au/TiO2 nanocomposite have been carried out using X-ray diffraction, field emission scanning electron microscope, transmission electron microscope, X-ray photoelectron spectroscopy and Raman spectroscopy. Furthermore, the meticulous comparative field emission characteristics of the aligned TiO2 nanotubes and Au/TiO2 nanocomposite have been performed. The turn-on field defined for the current density of 10 mu A/cm(2) has been found to be 3.9, 2.8, 3.2 and 3.7 V/mu m for specimen A, B, C and D, respectively. The observed low turn-on field of specimen B has been found to be superior than the other semiconducting nanocomposites reported in the literature. The emission current stability over a period of 3 h is found to be better for all the specimens. To the best of our knowledge, a systematic field emission study of Au/TiO2 nanocomposite has not been explored. The observed superior field emission study of Au/TiO2 nanocomposite indicates their possible use in micro/nanoelectronic devices.